Ebbs and Flows of Securities Fraud Litigation: Empirical Examination of Post-PSLRA Frequency & Severity Trends - Andrew Banasiewicz (Universitas Airlangga, 2022)
The separation of ownership and management that characterizes modern business corporations frequently gives rise to a conflict of interest known as agency dilemma. A manifestation of information asymmetry between organizational decision-makers – i.e., corporate directors and officers – and organizational owners/investors, that discord can spur formal allegations of incorrect, incomplete, misleading, or untimely management disclosures, ultimately leading to securities fraud litigation or simply shareholder litigation. For companies with distributed ownership spread across thousands of individual and institutional investors, securities lawsuits commonly encompass large pools or ‘classes’ of shareholders jointly pursuing their claims seeking financial compensation for management misinformation-caused losses; not surprisingly, those class actions stand out as one of the most economically and reputationally damaging manifestations of organizational risk. The research summarized here offers empirical assessment of the 25 years of securities class action filings and settlements that followed the passage of the seminal legislative act, the Private Securities Litigation Reform Act of 1995, yielding a number of unexpected shareholder litigation incidence and cost related conclusions.